Pattern and Cause of Road Traffic Accidents in Morang District - Poudel, Sudhan; Dhungana, Sudarshan; Dahal, Raksha (Journal of Nepal Health Research Council, 2021)
Background: Road traffic accidents is growing continuously as a global burden and would be a leading cause of death in developing countries. The global burden of road traffic accidents continues to grow and promises to overtake tropical diseases as leading causes of death in the developing world. This study aimed to study the pattern and causes of road traffic accidents in Morang district.Methods: Record based descriptive cross-sectional study was used by reviewing all registered RTA cases of the District Traffic Police Office, Morang during fiscal year 2074/75 (Shrawan 2074 to Ashad 2075). 501 road traffic accident cases were found in the record and used for the study. The data was analysed using SPSS v 16 and presented in normal frequency tables and crosstables.Results: Out of 501 accidents 32.2% occurred Friday and Saturday. In the evening time, most of the accidents occurred. In highways, 53.5% of accident cases occurred. 82% of the accidents occurred in blacktop road. Two-wheelers are mostly involved in accident cases (77%). Negligence (55.7%) and over-speed (36.5%) were the major reasons for accidents. In 33% of cases, accidents occurred involving pedestrians and cyclists. 80% of the drivers are below 40 years; similarly 80% of the victims are also below 40 years. Among victims who died 84.1% were male and among injured 73.3% were males.Conclusions: Weekends, evening, highways and two wheelers are more accident prone time, place and vehicles respectively. Overspeed and negligence of driver tends to major cause of accidents and majority of victims are the young bike riders and pedestrians. Keywords: Burden; causes; road traffic accidents; pattern